On the Role of Climate Forcing by Volcanic Sulphate and Volcanic Ash - Baerbel Langmann (Advances in Meteorology)
There is overall agreement that volcanic sulphate aerosols in the stratosphere can reduce solar radiation reaching the earth’s surface for years, thereby reducing surface temperatures, affecting global circulation patterns and generally the global climate system. However, the response of the climate system after large volcanic eruptions is not fully understood and global climate models have difficulties to reproduce the observed variability of the earth system after large volcanic eruptions until now. For geological timescales, it has been suggested that, in addition to the stratospheric climate forcing by volcanic sulphate aerosols, volcanic ash affects climate by modifying the global carbon cycle through iron fertilising the surface ocean and stimulating phytoplankton growth. This process has recently also been observed after the eruption of the volcano Kasatochi on the Aleutian Islands in summer 2008. To trigger future research on the effect of volcanic ash on the climate system via ocean iron fertilisation, this review paper describes the formation processes and atmospheric life cycles of volcanic sulphate and volcanic ash, contrasts their impact on climate, and emphasises current limitations in our understanding.